The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1115/1.2821989
|View full text |Cite
|
Sign up to set email alerts
|

Pipe Flow With Radial Inflow: Experimental and Modeling Work

Abstract: In this paper results are presented from experiments in which the pressure loss in single-phase pipe flow is studied when radial inflow occurs. Experiments have been carried out with pipes which have different perforation geometries so as to be able to investigate the effect of perforation geometry on the pressure loss. Data analysis of these experiments, as well as analysis of experiments carried out by other groups, yields a pressure loss model which accurately describes pressure losses in single-phase pipe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The upward component of flow past the screen may play an important role in reducing ssu$$ {s}_{su} $$ (well screen upflow loss) and should be a focus of further research. Schulkes et al (1999) suggest inflow jets may be beneficial to reduce the head loss. Further, Misstear et al (2017) sites work suggesting upflow head loss in screens may be the largest contributor of total well losses and screen entrance losses negligible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The upward component of flow past the screen may play an important role in reducing ssu$$ {s}_{su} $$ (well screen upflow loss) and should be a focus of further research. Schulkes et al (1999) suggest inflow jets may be beneficial to reduce the head loss. Further, Misstear et al (2017) sites work suggesting upflow head loss in screens may be the largest contributor of total well losses and screen entrance losses negligible.…”
Section: Discussionmentioning
confidence: 99%
“…According to Peterson et al (1955) "the drag in the well screen is almost entirely the result of the influence of the jets of water issuing from the screen openings, and the roughness coefficient of the screen itself can be neglected." However, Schulkes et al (1999) show upflow losses in screens are lower than those in blank pipe as inflow from slots actually displace the boundary layer at the wall, thus decreasing losses.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Su , found that the pressure drop of a variable mass flow primarily consists of four parts: friction pressure drop of the tube wall, acceleration, hole roughness, and mixed pressure drop. Schulkes, Yuan, and Zhou revealed that the pressure drop is related to the hole diameter, hole density, velocity, and angle of injection and obtained empirical formulas for the mixed pressure drop. Qu, Le, Shi, and Li studied two-phase transition mass flow and established a pressure drop model for multibranch wells.…”
Section: Introductionmentioning
confidence: 99%